(untitled) (International Integralize Scientific, 2026)
The implementation of New Public Governance is an essential strategy for addressing the challenges of administrative inefficiency and the growing demand for transparency and responsiveness in contemporary municipal management. This study analyzes the process of state modernization, based on the transition from traditional bureaucratic models to collaborative and integrated structures, seeking to understand how this paradigmatic shift impacts local administration. The overall objective is to investigate the effectiveness of public governance as an instrument for transforming municipal management. The methodology employed was based on a systematic literature review, in which 30 scientific articles were initially identified in the Scielo, PubMed, and Google Scholar databases, focusing on publications from the last five years. After rigorous screening for thematic relevance and inclusion criteria, 13 articles were selected for in-depth analysis and theoretical synthesis. The results demonstrate that the conversion of normative frameworks into practical management actions promotes direct benefits to the population’s quality of life, ensuring a more resilient, ethical, and efficient administrative system. It is concluded that the adoption of governance mechanisms is indispensable for strengthening public institutions, demonstrating that collaboration between the State and civil society results in public policies that are more aligned with real local needs. The study contributes to the field of administrative sciences by ratifying governance as a pillar of sustainability in municipal public management.